Relaciones sociales y comunidades en una plataforma virtual para cursos de programación de computadores - Leytón Yela, Ginna Viviana; Valencia, Astrid Johana; Bucheli Guerrero, Victor Andrés (Ingeniería, 2022)
Context: To identify the relationship between the students’ academic performance and the metrics of the graphs obtained corresponding to the interactions of the users in the Piazza platform. Method: The results obtained corresponding to the interactions between students and teachers in the Piazza platform are studied, carrying out a practical case of social network analysis through computational tools and definition of metrics. Results: The resulting information is a valuable support for the implementation of strategies in the content of a course assisted with virtual platforms, since the social structures that result from the different forms of relationship are identified, which allows mapping or analyzing the relationships between people, cooperation between actors, groups, or communities, among others. Conclusions: The metrics established to evaluate the social networks obtained from the platform allow teachers to determine the participation and interaction between students, identifying different patterns of interaction that define a relationship between the construction of social ties with the students’ academic performance.